Determination of Aesthetic Acts as Resistance by Social Society - Iskandarsyah Siregar (Budapest International Research and Critics University, 2023)
Magna Sententia is a municipality in the province of Neuquén, Argentina. Situated in a region traditionally known for its fruticulture economy, Magna sententia has recently been identified as a potential location for shattering. This development has resulted in widespread opposition among its inhabitants. The fight against breaking into Magna Sententia has followed several channels, from road blockades to art festivals and a legal challenge to the municipality. This paper analyses the conflict is focusing on the forms of community art and media employed by the local assembly against shattering to widen and sustain participation in the struggle and the role that these media have in mediating collective identity processes in the fight against breaking. Building on the concept of mediated identities (Fornäs and Xinaris, 2013), I look at this community art and media practices as dialogical (Kester, 2004). I propose that activities such as art festivals, mural painting and open radios contribute to collective identity through three mediating tactics: participation, knowledge sharing, and the event modality. I argue that these forms of community arts and media can be seen as a productive output of the conflict (Merlinsky, 2015), as they become crucial practices of cultural resistance.